Heterosis in horticultural crop breeding: combining old theoretical bases with modern genomic views - Farinati, Silvia; Scariolo, Francesco; Palumbo, Fabio; Vannozzi, Alessandro; Barcaccia, Gianni; Lucchin, Margherita (Frontiers in Horticulture, 2023)
Heterosis in plants has been among the challenging topics for plant scientists worldwide. The production of F1 hybrid varieties of seed-propagated horticultural species is one of the most successful applications of plant breeding techniques. The exploitation of the heterosis phenomenon promotes homogeneity and maximizes crop yields and is a way for breeders to legally control and protect their commercial products. In the past heterosis has been largely studied and explored in cereal crop systems, considering maize as a model for understanding the genetic bases of this phenomenon. To date, crossbreeding in horticultural vegetables has also rapidly progressed. F1 hybrid varieties are available for many horticultural crops, including both allogamous and autogamous species. Several genetic and nongenetic mechanisms have been applied to facilitate the large-scale production of F1 hybrid seeds in vegetable crops to prevent undesirable selfing. Although the development and commercialization of F1 hybrids is currently common in agriculture, this phenomenon is still being investigated at different levels. With the rapid accumulation of knowledge on plant genome structures and gene activities and the advancement of new genomics platforms and methodologies, significant progress has been achieved in recent years in the study of the genetic and molecular bases of heterosis. This paper provides a brief overview of current theoretical advances and practical predictions of the molecular mechanisms underlying heterosis in plants. The aim is to carefully summarize the fundamental mechanisms of heterosis in plants, focusing on horticultural plant breeding, to improve the existing knowledge in this research area. We describe the quantitative genetic model of phenotypic variation and combine evolutionary, phenotypic and molecular genetic views to explain the origin and manifestation of heterosis and its significance for breeding F1 hybrid varieties in horticultural crops. The principles of genomic prediction and its applications in genomic selection are then covered.